Analysis of two AL-amyloidosis cases reporters (own observations) - T. G. Shekhovtseva; M. A. Dolinna (Ukrainian Journal of Nephrology and Dialysis, 2019)
Abstract. According to current presentations, primary AL-amyloidosis (AL-A) and multiple myeloma, associated and not associated with AL-A, are considered as a part of uniform β-lymphocytic dislocation that is characterized by proliferation of abnormal clone of plasma or β-cells in the bone marrow with excess production of monoclonal immunoglobulins.Objective: to describe our own observations of patients with AL-A, which is an example of complexity of the disease diagnostics, due to the polymorphism of clinical picture and need for immunological verification.It was presented 2 cases of late AL-A diagnostics. Amyloid depositing in different organs determined the diversity of clinical manifestations. AL-A had a consistently progressive character with the gradual involvement of various organs and systems. Results: case 1 demonstrated AL-A with damage of kidneys, heart, liver, spleen, lungs, pleura and subsequent development of ischemic stroke. In the second case AL-amyloidosis with damage of heart, kidneys, lungs, tongue and skin was diagnosed. The severity of the patient's condition was due to severe nephrotic syndrome. AL-A is a serious disease that leads to a lethal end if treatment is not timely. Our observations demonstrate the complexity of AL-A diagnostics, which requires the collaboration of doctors of various profiles.Modern morphological diagnostics of amyloidosis involves not only detection but also mandatory amyloid typing, which determines further therapeutic tactics. Diagnostics of AL-A diagnosis should be based on the morphological study results. The final diagnosis of amyloidosis is established after congolic masses detecting. Biopsy of the affected organ is the most effective diagnostic method. When there is a nephrotic syndrome, kidney biopsy is most appropriate, because amyloid will be detected in 80% of AL-A. The most effective method for AL-A typing is an immunohistological study using the immunoglobulin light chains antisera.